2020
DOI: 10.3847/1538-3881/abacb6
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Stellar Stream Spectroscopic Survey (S5): Chemical Abundances of Seven Stellar Streams

Abstract: We present high-resolution Magellan/MIKE spectroscopy of 42 red giant stars in seven stellar streams confirmed by the Southern Stellar Stream Spectroscopic Survey (S 5): ATLAS, Aliqa Uma, Chenab, Elqui, Indus, Jhelum, and Phoenix. Abundances of 30 elements have been derived from over 10,000 individual line measurements or upper limits using photometric stellar parameters and a standard LTE analysis. This is currently the most extensive set of element abundances for stars in stellar streams. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 198 publications
4
94
4
Order By: Relevance
“…A list of studies have shown that these disrupted stellar systems, together with globular clusters and chemically peculiar stars with halo orbits, can be grouped based on similar orbital properties, suggestive of their common origins (Roederer et al 2018;Myeong et al 2018b;Myeong et al 2019;Naidu et al 2020;Yuan et al 2020b;Bonaca et al 2021;Limberg et al 2021;Gudin et al 2021;Li et al 2021a;Shank et al 2021). Detailed abundance studies for these stellar debris have been made possible by HRspectroscopic follow-up studies (Ji et al 2020;Aguado et al 2021a,b;Matsuno et al 2021;Gull et al 2021), as well as by HR-spectroscopic surveys, such as the GALactic Archaeology with HERMES survey (GALAH; Buder et al 2021;Simpson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A list of studies have shown that these disrupted stellar systems, together with globular clusters and chemically peculiar stars with halo orbits, can be grouped based on similar orbital properties, suggestive of their common origins (Roederer et al 2018;Myeong et al 2018b;Myeong et al 2019;Naidu et al 2020;Yuan et al 2020b;Bonaca et al 2021;Limberg et al 2021;Gudin et al 2021;Li et al 2021a;Shank et al 2021). Detailed abundance studies for these stellar debris have been made possible by HRspectroscopic follow-up studies (Ji et al 2020;Aguado et al 2021a,b;Matsuno et al 2021;Gull et al 2021), as well as by HR-spectroscopic surveys, such as the GALactic Archaeology with HERMES survey (GALAH; Buder et al 2021;Simpson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Elqui is on a high-energy radial orbit and appears unassociated with any of the Milky Way progenitors. Ji et al (2020) found significant metallicity spread in Elqui, a telltale signature of a dwarf galaxy origin with an extended star-formation history. Elqui could plausibly have been a satellite of GSE, but we disfavor this association because GSE accreted ≈ 10 Gyr ago (Bonaca et al 2020c) and disruption of satellites on radial orbits is fast.…”
Section: Association With Disrupted Galaxiesmentioning
confidence: 90%
“…At slightly lower energies and on prograde orbits, Jhelum and Indus are two streams that have been linked together based on their 3D orbits (Bonaca et al 2019a). Curiously, they have similar metallicities ([Fe/H]≈ −2.1) and detectable spread in chemical abundances (Ji et al 2020), which suggests they are tidal debris from the same dwarf galaxy at different orbital phases, possibly from separate pericenter passages. This region of phase space is occupied by debris from Helmi 1 and Wukong; we therefore suggest that Jhelum and Indus may represent the remaining coherent debris from either of these galaxies.…”
Section: Association With Disrupted Galaxiesmentioning
confidence: 99%
“…The data were reduced with CarPy (Kelson 2003). The spectra were analyzed using SMHR 2 , which provides an interface to doppler correct, normalize and stitch orders, fit equivalent widths, interpolate Castelli & Kurucz (2004) stellar atmospheres, and run MOOG including scattering opacity (Sneden 1973;Sobeck et al 2011) and Barklem et al (2000) damping 3 to determine abundances from equivalent widths and spectrum synthesis (see Ji et al 2020 for a detailed description).…”
Section: Observations and Abundance Analysismentioning
confidence: 99%